Field-realistic exposure to the androgenic endocrine disruptor 17β-trenbolone alters ecologically important behaviours in female fish across multiple contexts. (December 2018) - Bertram, Michael G.; Saaristo, Minna; Martin, Jake M.; Ecker, Tiarne E.; Michelangeli, Marcus; Johnstone, Christopher P.; Wong, Bob B.M.
Abstract: The capacity of pharmaceutical pollution to alter behaviour in wildlife is of increasing environmental concern. A major pathway of these pollutants into the environment is the treatment of livestock with hormonal growth promotants (HGPs), which are highly potent veterinary pharmaceuticals that enter aquatic ecosystems via effluent runoff. Hormonal growth promotants are designed to exert biological effects at low doses, can act on physiological pathways that are evolutionarily conserved across taxa, and have been detected in ecosystems worldwide. However, despite being shown to alter key fitness-related processes (e.g., development, reproduction) in various non-target species, relatively little is known about the potential for HGPs to alter ecologically important behaviours, especially across multiple contexts. Here, we investigated the effects of exposure to a field-realistic level of the androgenic HGP metabolite 17β-trenbolone—an endocrine-disrupting chemical that has repeatedly been detected in freshwater systems—on a suite of ecologically important behaviours in wild-caught female eastern mosquitofish ( Gambusia holbrooki ). First, we found that 17β-trenbolone-exposed fish were more active and exploratory in a novel environment (i.e., maze arena), while boldness (i.e., refuge use) was not significantly affected. Second, when tested for sociability, exposed fish spent less time in close proximity to a shoal of stimulus (i.e., unexposed) conspecific females and were, again, found to be more active. Third, when assayed for foraging behaviour, exposed fish were faster to reach a foraging zone containing prey items (chironomid larvae), quicker to commence feeding, spent more time foraging, and consumed a greater number of prey items, although the effect of exposure on certain foraging behaviours was dependent on fish size. Taken together, these findings highlight the potential for exposure to sub-lethal levels of veterinary pharmaceuticals to alter sensitive behavioural processes in wildlife across multiple contexts, with potential ecological and evolutionary implications for exposed populations. Graphical abstract: Image 1 Highlights: Use of growth-promoting veterinary pharmaceuticals is widespread in global beef production. The androgenic growth promotant metabolite 17β-trenbolone (17β-TB) is present in aquatic systems. Adult female mosquitofish were exposed to 17β-TB at an environmentally realistic level. Exposed females were more active and exploratory, less social, showed increased foraging behaviour. Androgenic contaminant disrupts key fitness-related behaviours in female fish. Abstract : The androgenic endocrine disruptor 17β-trenbolone alters behaviour in female fish across multiple fitness-related contexts.